(untitled) (KEMANUSIAAN The Asian Journal of Humanities, 2014)
This paper examines the evolution of Sufi institutions from the realm of the mosque institutions to the independent and self-governing bodies and establishments that cater to the needs of the ever-proliferating Sufi community. The relationship between Sufi institutions and other Islamic socio-political, educational and religious institutions is also discussed. The focus of the paper is, first, on the historical needs of the Sufi, which called for the creation of self-governing Sufi institutions. This examination is followed by a discussion of the Sufi notion of travel and how this important Sufi tradition facilitated the gradual emergence of Sufi institutions. Then, the emergence of Sufi institutions from simple duwayrahs (small houses or convents) to ribats and multipurpose khanqah complexes is examined.